Anti-scorpion venom activity of Thapsia garganica methanolic extract: Histopathological and biochemical evidences. (30th January 2018) - Bouimeja, Btissam; El Hidan, Moulay Abdelmonaim; Touloun, Oulaid; Ait Laaradia, Mehdi; Ait Dra, Loubna; El Khoudri, Noureddine; Chait, Abderrahman; Boumezzough, Ali
Abstract: Ethnopharmacological relevance: Thapsia garganica, is a herbal medicine traditionally used as diuretic, emetic and purgative. It is also used as anti-scorpion venom in Morocco; however, its protective effects against scorpion venom remain elusive. Aim of the study: The present study was undertaken to evaluate anti-venom activity of T. garganica in vivo through histological and biochemical studies. Materials and methods: Methanolic leaves extract of T. garganica was evaluated for anti-venom activity against buthus. occitanus under in vivo conditions. Histopathological and biochemical changes in envenomed and treated mice were also examined. Phytochemical screening was conducted to estimate the major constituents whereas DPPH, β -Carotene–linoleic acid and reducing power assays were performed to evaluate the anti-oxidant activity of T. garganica extract. Results: Methanolic leaves extract of T. garganica (2 g/kg) increased the survival time (> 18 h) of mice injected with lethal doses of B. occitanus venom, with remarkable recovery of histology damage. Furthermore T. garganica induced a significant decreased of biochemical markers of kidney, liver and heart function. Phytochemistry screening revealed the presence of phenolic compounds, flavonoids, tannins and steroids/terpenoids, which might explain the bioactivity of the extract. It was also shown that the extract has an exceptionally high antioxidant activity compared to well-known antioxidants used as standards. Conclusion: The present study provides strong evidence that support the use of T. garganica as anti-scorpion venom in traditional medicine in Morocco. However, additional studies are required to isolate and identify the metabolites responsible for the activity. Graphical abstract: